2022
DOI: 10.3390/ijerph191711017
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness and HbA1c: Association Mediated by Insulin Resistance in Hispanic Adults

Abstract: Arterial stiffness may be associated with glucose metabolism parameters, such as HbA1c, mainly via insulin resistance. We aimed to investigate the association between arterial stiffness and HbA1c and explore the mediator effect of insulin resistance. In this cross-sectional study, arterial stiffness (pulse-wave velocity; PWV), HbA1c, and insulin resistance (METS-IR) were determined in Hispanic adults. In addition to sex and age, various biochemical measurements (glucose, lipid profile, etc.) and adipose tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…Moreover, several studies concluded that HbA1c was related to PWV independent of conventional cardiovascular risk factors such as age and blood pressure, a finding that was in line with our results 35,36 . Various mechanisms have been proposed to link HbA1c with the development of atherosclerosis, including through insulin resistance due to endothelial dysfunction and an abnormal insulin vasodilative effect mediated by endothelium‐derived nitric oxide 37 . All these alterations may contribute to the development and progression of atherosclerosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, several studies concluded that HbA1c was related to PWV independent of conventional cardiovascular risk factors such as age and blood pressure, a finding that was in line with our results 35,36 . Various mechanisms have been proposed to link HbA1c with the development of atherosclerosis, including through insulin resistance due to endothelial dysfunction and an abnormal insulin vasodilative effect mediated by endothelium‐derived nitric oxide 37 . All these alterations may contribute to the development and progression of atherosclerosis.…”
Section: Discussionsupporting
confidence: 91%
“…35,36 Various mechanisms have been proposed to link HbA1c with the development of atherosclerosis, including through insulin resistance due to endothelial dysfunction and an abnormal insulin vasodilative effect mediated by endothelium-derived nitric oxide. 37 All these alterations may contribute to the development and progression of atherosclerosis. Future studies are needed to investigate T A B L E 3 Hazard ratios (95% CI) of the association between cfPWV, faPWV, and afSG and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The association between HbA1c, an indicator of long-term blood glucose regulation, and aortic stiffness seems to be constrained in certain studies [41][42][43].…”
Section: Correlations Between Aortic Elasticity Indices and Diabetic ...mentioning
confidence: 99%